The boy who failed show and tell - Sonnenblick, Jordan (Scholastic Press, 2021)
An unbelievably hilarious middle-grade true story from bestselling author Jordan Sonnenblick. In a typical school year, every kid has one or two things go wrong. But for Jordan, there's A LOT going wrong ALL THE TIME. By keeping his cool (some of the time), banging on the drums (a lot), and keeping his sense of humor (all the time), Jordan's going to try to make it through the year . . . and grow up to write a book about it! -- adapted from Amazon.com.